(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
19th century was a phase of significant intellectual excitement as well as a very important time in the history of modern India. Reeling under the political and economic burden of British conquest, Indian society changed gradually. Accepted values were being questioned. In this unsettled background, there was an urgent need for reform and regeneration of its institutions. In this mentioned context, present paper reorients the relationship between Raja Rammohan Roy and Henry Louis Vivian Derozio, two renown progressive person (social reformer) during the Bengal Renaissance in 19th century. Bengal Renaissance became a phenomenon in the colonial era in the sphere of society, education, religion so on and so forth. This paper attempts to evaluate a comparative discussion between Rammohan Roy and Derozio in order to understand their nature of work and to provide a critical analysis of this phenomenon.